Pigs in heaven : a novel - Kingsolver, Barbara (New York : HarperPerennial, 1994)
Six-year-old Turtle Green witnesses a freak accident drawing her and her mother into a conflict of historic proportions.
Adult
Adult
Wilson's Senior High School
Wilson's Fiction
School Library Journal
910
Keywords: Mothers and daughters -- Fiction; Adopted children -- Fiction; Cherokee Indians -- Fiction; Mother-daughter relationship -- Fiction; Adopted children -- Fiction; Cherokee Indians -- Fiction; Domestic fiction; Love stories; Domestic fiction; Love stories